Synthesis of Goethite (α-FeOOH) Pigment by Precipitation Method from Iron Lathe Waste - Lilik Miftahul Khoiroh; Elysia Dwi Nuraini; Nur Aini (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2018)
Lathe waste contains high iron content potential to be further processed into goethite pigment. The purpose of the research was to determine the effect of synthesis temperature on the structure, colour values, and morphology of goethite pigment. The synthesis was conducted with temperature variations of 60, 70, 80and 90°C. The XRD diffraction pattern shows that crystal structure of the product of all synthesis temperatures are goethite (α-Fe-OOH) with orthorhombic structure. The crystal size of the pigment ranges between 11.17 – 12.32 nm. Colour value analysis shows that product of 70°C synthesis temperature exhibits the highest lightness value about 40.5. Based on SEM-EDX imaging, the morphology of the samples is not uniform and forming agglomerates. Traces of impurities were detected, such as C and Na. Keywords: Iron lathe waste, goethite, temperature, precipitation